(x-1,2)^2=4
(x+1)^3=-125
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\frac{2}{3}+\frac{7}{4}:x=\frac{5}{6}\)
\(\Leftrightarrow\frac{7}{4}:x=\frac{5}{6}-\frac{2}{3}\)
\(\Leftrightarrow\frac{7}{4}:x=\frac{1}{6}\)
\(\Leftrightarrow x=\frac{21}{2}\)
\(b,\left(x+\frac{5}{3}\right).\left(x-\frac{5}{4}\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x+\frac{5}{3}=0\\x-\frac{5}{4}=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\frac{5}{3}\\\frac{5}{4}\end{matrix}\right.\)
\(c,\left(x-1,2\right)^2=4\)
\(\Leftrightarrow\left[{}\begin{matrix}x-1,2=2\\x-1,2=-2\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3,2\\x=-0,8\end{matrix}\right.\)
\(d,\left(x+1\right)^3=-125\)
\(\Leftrightarrow\left(x+1\right)^3=\left(-5\right)^3\)
\(\Leftrightarrow x+1=-5\)
\(\Leftrightarrow x=-6\)
Vậy ...........................................................
\(\left(x-1,2\right)^2=4\)
⇔\(x^2-2.x.1,2+1,2^2=4\)
⇔\(x^2-2,4x+1,44=4\)
⇔\(x^2-2,4x=4-1,44\)
⇔\(x\left(x-2,4\right)=2,56\)
⇔\(x=2,56\) hoặc \(x-2,4=2,56\)
⇔\(x=2,56\) hoặc \(x=4,96\)
a) \(\left(x-1,2\right)^2=4=2^2\)
\(\Leftrightarrow x-1,2=4\)
\(\Leftrightarrow x=5,2\)
b) \(\left(x+1\right)^3=-125=\left(-5\right)^3\)
\(\Leftrightarrow x+1=-5\)
\(\Leftrightarrow x=-6\)
c) \(\left(x+1,5\right)^8+\left(2,7-y\right)^{10}=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}x+1,5=0\\2,7-y=0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=-1,5\\y=2,7\end{matrix}\right.\)
a, 125 x 1,2 + 1,2 x 874 + 1,2
=125 x 1,2 + 1,2 x 874 + 1,2 x 1
= 1,2 x (125+874+1)
= 1,2 x 1000
= 1200
b, 24,369 x 99+24,369 x (7:4 - 0,75)
= 24,369 x 99 + 24,369 x (1,75-0,75)
= 24,369 x 99 + 24,369 x 1
= 24,369 x (99+1)
= 24,369 x 100
= 2436,9
\(a,125\times1,2+1,2\times874+1,2\\ =\left(125+874+1\right)\times1,2\\ =1000\times1,2\\ =1200\\ b,24,369\times99+24,369\times\left(7:4-0,75\right)\\ =24,369\times99+24,369\times\left(1,75-0,75\right)\\ =24,369\times99+24,369\times1\\ =24,369\times\left(99+1\right)\\ =24,369\times100\\ =2436,9\)
a) \(2^x=8\)
⇔ \(2^x=2^3\)
⇒ \(x=3\)
b) \(3^x=27\)
⇔ \(3^x=3^3\)
⇒ \(x=3\)
c) \(\left(-\dfrac{1}{2}\right)x=\left(-\dfrac{1}{2}\right)^4\)
⇔ \(x=\left(-\dfrac{1}{2}\right)^4\div\left(-\dfrac{1}{2}\right)\)
⇔ \(x=\left(-\dfrac{1}{2}\right)^3\)
d) \(x\div\left(-\dfrac{3}{4}\right)=\left(-\dfrac{3}{4}\right)^2\)
⇔ \(x=\left(-\dfrac{3}{4}\right)^2\cdot\left(-\dfrac{3}{4}\right)\)
⇔ \(x=\left(-\dfrac{3}{4}\right)^3=-\dfrac{27}{64}\)
d) \(\left(x+1\right)^3=-125\)
⇔ \(\left(x+1\right)^3=\left(-5\right)^3\)
⇔ \(x+1=-5\)
⇔ \(x=-5-1=-6\)
2:
a: (x-1,2)^2=4
=>x-1,2=2 hoặc x-1,2=-2
=>x=3,2(loại) hoặc x=-0,8(loại)
b: (x-1,5)^2=9
=>x-1,5=3 hoặc x-1,5=-3
=>x=-1,5(loại) hoặc x=4,5(loại)
c: (x-2)^3=64
=>(x-2)^3=4^3
=>x-2=4
=>x=6(nhận)
a: x^3=7^3
=>x^3=343
=>\(x=\sqrt[3]{343}=7\)
b: x^3=27
=>x^3=3^3
=>x=3
c: x^3=125
=>x^3=5^3
=>x=5
d: (x+1)^3=125
=>x+1=5
=>x=4
e: (x-2)^3=2^3
=>x-2=2
=>x=4
f: (x-2)^3=8
=>x-2=2
=>x=4
h: (x+2)^2=64
=>x+2=8 hoặc x+2=-8
=>x=6 hoặc x=-10
j: =>x-3=2 hoặc x-3=-2
=>x=1 hoặc x=5
k:
9x^2=36
=>x^2=36/9
=>x^2=4
=>x=2 hoặc x=-2
l:
(x-1)^4=16
=>(x-1)^2=4(nhận) hoặc (x-1)^2=-4(loại)
=>x-1=2 hoặc x-1=-2
=>x=3 hoặc x=-1
a: \(\Leftrightarrow4^{x-5}\cdot17=68\)
=>4^x-5=4
=>x-5=1
=>x=6
b: \(\Leftrightarrow\dfrac{1}{3}:\left|2x-1\right|=\dfrac{1}{3}+\dfrac{2}{3}=1\)
=>|2x-1|=1/3
=>2x-1=1/3 hoặc 2x-1=-1/3
=>x=2/3 hoặc x=1/3
c: =>|2x-2|=|3x+15|
=>3x+15=2x-2 hoặc 3x+15=-2x+2
=>x=-17 hoặc x=-13/5
1. \(\left(x+1\right)^3-125\)
\(=\left(x+1\right)^3-5^3\)
\(=\left(x+1-5\right).\left[\left(x+1\right)^2+\left(x+1\right).5+5^2\right]\)
2. \(\left(x+4\right)^3-64\)
\(=\left(x+4\right)^3-4^3\)
\(=\left(x+4-4\right).\left[\left(x+4\right)^2+\left(x+4\right).4+4^2\right]\)
3. \(x^3-\left(y-1\right)^3\)
\(=(x^3-y+1).\left[\left(x^2\right)+x.\left(y+1\right)+\left(y+1\right)^2\right]\)
\(\)4. \(\left(a+b\right)^3-c^3\)
\(=\left[\left(a+b\right)-c\right].\left[\left(a+b\right)^2+\left(a+b\right).c+c^2\right]\)
5. \(125-\left(x+2\right)^3\)
\(=5^3-\left(x+2\right)^3\)
\(=\left(5-x-2\right).\left[5^2+5.\left(x+2\right)+\left(x+2\right)^2\right]\)
6. \(\left(x+1\right)^3+\left(x-2\right)^3\)
\(=\left[\left(x+1\right)+\left(x-2\right)\right].\left[\left(x+1\right)^2-\left(x+1\right).\left(x-2\right)+\left(x-2\right)^2\right]\)
\(x^4=x\)
\(\Rightarrow x=1\)
\(\left(2x+1\right)^3=125\)
\(\Rightarrow\left(2x+1\right)^3=5^3\)
\(\Rightarrow2x+1=5\)
\(\Rightarrow2x=5-1=4\)
\(\Rightarrow x=4:2=2\)
\(2^{3x}+4=132\)
\(\Rightarrow2^{3x}=132-4=128\)
\(\Rightarrow2^{3x}=2^7\)
\(\Rightarrow3x=7\)
\(\Rightarrow x=7:3=\frac{7}{3}\)
\(\left(x-1,2\right)^2=4\)
\(\left(x-1,2\right)^2=2^2\)
\(\Rightarrow\orbr{\begin{cases}x-1,2=2\\x-1,2=-2\end{cases}\Rightarrow\orbr{\begin{cases}x=3,2\\x=-0,8\end{cases}}}\)
\(\left(x+1\right)^3=-125\)
\(\left(x+1\right)^3=\left(-5\right)^3\)
\(x+1=-5\)
\(x=-6\)
\(a,\left(x-1,2\right)^2=4\)
\(x-1,2=\pm2\)
\(\orbr{\begin{cases}x-1,2=2\\x-1,2=-2\end{cases}\Rightarrow\orbr{\begin{cases}x=3,2\\x=-\frac{4}{5}\end{cases}}}\)
\(b,\left(x+1\right)^3=-125\)
\(x+1=-5\)
\(x=-6\)